Incidence and clinical manifestations of giant cell arteritis in Spain: results of the ARTESER register - Santos Castañeda; Ricardo Blanco; Héctor Corominas; Patricia Carreira; Ivan Castellví; Eugenio De Miguel; Javier Narváez; Judit LLuch; Ivette Casafont-Solé; Jose María Pego; Lydia Abasolo; Carmen Larena; et al. (RMD Open)
Objective This study aimed to estimate the incidence of giant cell arteritis (GCA) in Spain and to analyse its clinical manifestations, and distribution by age group, sex, geographical area and season.Methods We included all patients diagnosed with GCA between 1 June 2013 and 29 March 2019 at 26 hospitals of the National Health System. They had to be aged ≥50 years and have at least one positive results in an objective diagnostic test (biopsy or imaging techniques), meet 3/5 of the 1990 American College of Rheumatology classification criteria or have a clinical diagnosis based on the expert opinion of the physician in charge. We calculated incidence rate using Poisson regression and assessed the influence of age, sex, geographical area and season.Results We identified 1675 cases of GCA with a mean age at diagnosis of 76.9±8.3 years. The annual incidence was estimated at 7.42 (95% CI 6.57 to 8.27) cases of GCA per 100 000 people ≥50 years with a peak for patients aged 80–84 years (23.06 (95% CI 20.89 to 25.4)). The incidence was greater in women (10.06 (95% CI 8.7 to 11.5)) than in men (4.83 (95% CI 3.8 to 5.9)). No significant differences were found between geographical distribution and incidence throughout the year (p=0.125). The phenotypes at diagnosis were cranial in 1091 patients, extracranial in 337 patients and mixed in 170 patients.Conclusions This is the first study to estimate the incidence of GCA in Spain at a national level. We found a predominance among women and during the ninth decade of life with no clear variability according to geographical area or seasons of the year.